2022
DOI: 10.37190/ppmp/153944
|View full text |Cite
|
Sign up to set email alerts
|

Physical restrictions of the flotation of fine particles and ways to overcome them

Abstract: This work analyses the basic problems of the fine particles flotation and suggests new ways to overcome them. It is well accepted that the poor recovery of fine particles is due to the small collision rate between them and the bubbles due to the significant difference between their sizes. This common opinion is based on a theory, assuming in its first version a laminar regime, but later has been advanced to intermediate turbulence. It accepts that the particles are driven by the streamlines near the bubbles. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Another reason can be the nature of fine and ultrafine particles as the collector rubbers and their readily high collector dosage requirements for being recovered. Further reasons for poor recovery of fine and ultrafine particles can be found elsewhere [43,44]. However, since the H-16 cell provided a high shear intensity on the aerator, the surface oxidation layers as well as slime coatings could be removed, which led to favorable adsorption of reagents on the particle surfaces and ultimately grade and recovery improvements.…”
Section: Results Of Industrial Surveysmentioning
confidence: 99%
“…Another reason can be the nature of fine and ultrafine particles as the collector rubbers and their readily high collector dosage requirements for being recovered. Further reasons for poor recovery of fine and ultrafine particles can be found elsewhere [43,44]. However, since the H-16 cell provided a high shear intensity on the aerator, the surface oxidation layers as well as slime coatings could be removed, which led to favorable adsorption of reagents on the particle surfaces and ultimately grade and recovery improvements.…”
Section: Results Of Industrial Surveysmentioning
confidence: 99%
“…Fortunately, there is another more realistic theoretical approach (e.g., [17,18]) accounting for the bubble-particle collisions under high turbulence. This theoretical approach predicts a significantly higher frequency of collisions [13,17]. A recent work of ours [13] concluded that the problem consists of the low efficiency of the collisions.…”
Section: Introductionmentioning
confidence: 84%
“…This theoretical approach predicts a significantly higher frequency of collisions [13,17]. A recent work of ours [13] concluded that the problem consists of the low efficiency of the collisions. Analysis based on the capillary theory of Scheludko et al [19] indicated the existence of a thermodynamic lower size limit of the fine particles to float [13] in the nano-scale range, which is weakly dependent on the size of the bubbles.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, the interaction between PPG600 and DAH led to a mutual synergistic effect, resulting in enhanced froth performance. This in turn resulted in finer bubble sizes, which affected the flotation recoveries of very fine particles [49][50][51][52][53].…”
Section: Micro-flotation Experimentsmentioning
confidence: 99%